2021
DOI: 10.3389/fcomp.2021.728801
|View full text |Cite
|
Sign up to set email alerts
|

Automated Student Group Collaboration Assessment and Recommendation System Using Individual Role and Behavioral Cues

Abstract: Early development of specific skills can help students succeed in fields like Science, Technology, Engineering and Mathematics. Different education standards consider “Collaboration” as a required and necessary skill that can help students excel in these fields. Instruction-based methods is the most common approach, adopted by teachers to instill collaborative skills. However, it is difficult for a single teacher to observe multiple student groups and provide constructive feedback to each student. With growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…For example, researchers have also illustrated the potential of deep learning for estimating collaboration aspects (Spikol et al, 2018). Furthermore, prior research has also shown the potential of deep learning models to utilize histogram-based feature representation of students' participation to assess collaboration quality (Som et al, 2021). Ma and colleagues (2023) in their recent study also showcased the ability of deep learning models to perform gracefully in the presence of noise.…”
Section: Rq2: Which ML Algorithms Show More Robust Performance In The...mentioning
confidence: 97%
“…For example, researchers have also illustrated the potential of deep learning for estimating collaboration aspects (Spikol et al, 2018). Furthermore, prior research has also shown the potential of deep learning models to utilize histogram-based feature representation of students' participation to assess collaboration quality (Som et al, 2021). Ma and colleagues (2023) in their recent study also showcased the ability of deep learning models to perform gracefully in the presence of noise.…”
Section: Rq2: Which ML Algorithms Show More Robust Performance In The...mentioning
confidence: 97%